Becoming of direction of Electrical measurement instrument-making is in the Kharkiv polytechnic institute (1950-1960) - Tverytnykova, O. Ye. (History of science and technology, 2013)
The article considers the contribution of scientists Kharkov Institute of Technology in the deployment of scientific research in the field of electrical measurements in Ukraine. Shown main stages of the formation of the scientific school of applied research within higher education.